COMPARATIVE ANALYSIS OF RICE FARMING INCOMEORGANIC AND NON-ORGANIC IN EAST OKU REGENCY - Juni, Juni; Rini Efrianti,; Fifian, Fifian Permata Sari (International Journal of Social Science, 2022)
This study aims to analyze the income of organic and non-organic rice farming in Ogan Komering Ulu Timur Regency. The research method used is a survey method. The research was conducted on March 2022 in East OKU Regency. The sampling method used an unequal layered random sample method in which a population of 374 lowland rice farmers was taken using the slovin formula with a margin of error of 10% and the sample taken was 37 respondents, and 20 organic rice farmers, so the total sample is 57 people. Testing and processing of research data using statistical analysis of T test or difference test (t-test) with two averages (parired – samples T-Test) using SPSS 23. The results showed that there was a difference in income between organic rice farmers of Rp. 21. 930,748,- per year and the income of non-organic paddy rice farmers is Rp.21,411,372,- per year. Even though mathematically the household income of organic farmers is greater than the household income of non-organic farmers, statistically there is no significant or no significant difference between the income received by organic and non-organic farmers.